Exp erimental research of wearable artificial kidney - N. A. Bazaev; V. M. Grinvald; S. V. Selishchev; A. V. Kalinov; A. V. Kozachuk; V. V. Kosatkin; F. F. Tyunder; D. V. Federyakin (Вестник трансплантологии и искусственных органов)
Aim. The article presents the results of wearable artificial kidney (WAK) biomedical trial based on peritoneal dialysis with continuous dialysate regeneration.Materials and methods. The trial was carried out on a 15-kg dog. First stage: dialysis was carried out on healthy dog to evaluate effect of WAK on blood biochemical indicators. Second stage: 200 ml of X-ray contrast agent was injected into dog’s bloodstream to simulate acute kidney failure.Results. During trial (39.5 hours) WAK was performing continuous peritoneal dialysis with dialysis fluid regeneration. During second stage (34 hours) creatinine and uric acid were eliminated from dialysis solution at the rate of 0.3 mg/h, urea was eliminated at the rate of 0.15 g/h, total removed ultrafiltrate volume was 350 ml. At the end of the second stage blood biochemical indicators stabilised in the range of normal values.Conclusion. Developed WAK can perform continuous blood purification and ultrafiltration with no pathologic impact on blood biochemical indicators.